Synthesis and Characterization of Nickel(II) Complexes with Azide Ion and Pyridine Derivatives as Ligands - RAMACHANDRAMOORTHY, T.; PAUL RAJ, A.; SIVASANKAR, V.; RAJAM, SHAMEELA (Asian Journal of Chemistry, 2010)
Nickel(II) complexes of the type [Ni(N3)2(X)3]2, where X = pyridine/2-picoline/3-picoline/4-picoline have been prepared and characterized on the basis of physico-chemical methods. The magnetic susceptibility data reveals that the complexes are high spin and six-coordinate with octahedral geometry. The spectroscopic data of these complexes show that they exist in the form of dimers with distorted octahedral structure. The analytical, magnetic moment and spectral data along with the geometry of nickel(II) complexes are discussed in the paper. The green coloured nickel(II) complexes correspond to the dimeric formulae: [Ni(N3)2 (py)3]2, [Ni(N3)2(2-pic)3]2, [Ni(N3)2(3-pic)3]2 and [Ni(N3)2(4-pic)3]2.